Methotrexate-Induced Accumulation of Fluorescent Annexin V in Collagen-Induced Arthritis - Andreas Wunder; Eyk Schellenberger; Umar Mahmood; Alexei Bogdanov; Ulf Müller-Ladner; Ralph Weissleder; Lee Josephson (Molecular Imaging)
We examined the accumulation of Cy5.5-labeled annexin V in the paws of mice with and without collagen-induced arthritis, with and without methotrexate (MTX) treatment, by near-infrared fluorescence imaging. Fluorescence reflectance imaging (FRI) of paws was performed 48 hr after MTX injection and at 10 min and 3 hr after the injection of Cy5.5-annexin V (1 nmol dye per mouse). With arthritic paws, MTX treatment caused a 7-fold increase in fluorescence intensity compared with the paws of untreated mice and a 4-fold increase compared to nonarthritic paws of MTX-treated mice ( p < .001 each). Tissue samples of paws were examined histologically for Cy5.5 fluorescence and by TUNEL staining for apoptosis. Cy5.5-annexin V was seen in the hyperplastic synovia of MTX-treated mice, and TUNEL staining for apoptosis showed apoptotic cells in the hyperplastic synovia. Monitoring the uptake of Cy5.5-annexin V in arthritic paws by FRI provided a method of assessing a response to MTX, a response that was readily quantitated with simple instrumentation and that occurred before conventional measurements of treatment response.